2018
DOI: 10.1016/j.cnp.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Modified motor unit number index (MUNIX) algorithm for assessing excitability of alpha motor neuron in spasticity

Abstract: HighlightsMotor unit number of the rectus femoris muscle in spasticity is measured by using the MUNIX algorithm.Ideal Case Motor Unit Count (ICMUC) can be used for comparing voluntary force production between spasticity and healthy volunteers.The modified MUNIX (MUNIXT) algorithm is a potential marker for increasing the excitability of alpha motor neuron pool in spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…In another study done by Serkan Uslu et al (2016) has concluded that the relationship between tendon tapping force and ordinal DTR grading was difficult to establish. 31 Our study also could not able to find the association between tendon tapping force and desired PTR variables. The mass of the hammer (200 g) was constant throughout the study which may not be a confounding factor.…”
Section: Discussioncontrasting
confidence: 57%
“…In another study done by Serkan Uslu et al (2016) has concluded that the relationship between tendon tapping force and ordinal DTR grading was difficult to establish. 31 Our study also could not able to find the association between tendon tapping force and desired PTR variables. The mass of the hammer (200 g) was constant throughout the study which may not be a confounding factor.…”
Section: Discussioncontrasting
confidence: 57%
“…High density surface EMG can recover information on MU recruitment [18,19], but the recording system is cumbersome, and data storing and processing are intensive. As a result, few EMG channels are preferred in many applied fields, such as sport [40], gait analysis [41], ergonomic assessments [42], diagnosis [31,43], myoelectric control [44]. It is then important to be able to extract more information from single channel recordings, going beyond basic analysis, such as the estimation of activity intervals or amplitude and spectral indexes.…”
Section: Discussionmentioning
confidence: 99%